An Organic Redox Mediator with a Defense‐Donor for Lithium Anode in Lithium–Oxygen Batteries. Issue 2 (23rd December 2022) - Sun, Zongqiang; Tan, Yanyan; Zhan, Yingjie; Li, Kaixuan; Dou, Wenjie; Wang, Chutao; Lin, Xiaodong; Yuan, Ruming; Yan, Jiawei; Zheng, Mingsen; Dong, Quanfeng
Abstract: Lithium–oxygen batteries (LOBs) suffer from large charge overpotential and unstable Li metal interface, which can be attributed to the inefficient charge transport at the insulating Li2 O2 /cathode interface and the severe oxygen corrosion issue on the Li anode surface. The use of soluble redox mediators (RMs) can effectively enhance the charge transport between Li2 O2 and cathode, thus greatly reducing the charge overpotential. However, oxidized RMs will also shuttle to the anode side and react with the Li metal, which not only results in the loss of both the RMs and the electrical energy efficiency but also exacerbates the Li anode corrosion. Herein, an organic compound—acetylthiocholine iodide (ATCI), in which a big cation group is contained, is proposed as a defense‐donor RM for lithium anode in LOBs to simultaneously address the above issues. During charge, it can accelerate the oxidation kinetics of Li2 O2 via its iodide anion redox couple (I − /I3 − ). Meanwhile, its cation segment (ATC + ) can move to the anode surface via electric attraction and in situ forms a protective interfacial layer, which prevents the Li anode from the attack of oxidized RM and oxygen species. Consequently, the ATCI‐containing LOBs can achieve both a low charge potential (≈3.49 V) and a long cycle life (≈190 cycles). Abstract : A nitrogen, sulfur‐containing organic iodide—acetylthiocholine iodide (ATCI) is first proposed as a defense‐donor redox mediator (RM) to simultaneously address the large charge overpotential and unstable Li metal interface issues in Li−O2 batteries. As a result, the ATCI‐containing Li−O2 batteries show excellent performance, with a low charge potential and a prolonged cycle life.